An optical tunable fiber filter based on the concatenated single-mode optical fibers with different cut-off wavelengths - Wanvisa Talataisong (2018)
In this study, an optical fiber tunable filter in visible wavelengths is studied. The structure of the proposed filter is simply fabricated by splicing different single-mode optical fiber having different cut-off wavelength together. The working principle of the filter is based on the cladding mode coupling to the high order mode introduced by disturbance on a single mode fiber in the filtering system. The experimental results clearly show that the concatenated single-mode optical fiber can act as the optical fiber tunable filter.